Поняття і види політичних ризиків - Демчук, Д. В.; Демчук, Д. В.; Demchuk, D. (My University, 2012)
This article provides an analysis of political risk from point of view of political actors. A classifi cation of political risk, main problematic aspects of managing political risk are defi ned.
Демчук Д. В. Поняття і види політичних ризиків / Д. В. Демчук // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України ; НУ ОЮА. – Одеса : Фенікс, 2012. – Вип.. 46. – С. 248-255.
Keywords: політичний ризик; діяльність політичних акторів; управління політичними ризиками; политический риск; деятельность политических актеров; управление политическими рисками; political risk; the activities of political actors; management of political risks